6+a-12=2

Simple and best practice solution for 6+a-12=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+a-12=2 equation:


Simplifying
6 + a + -12 = 2

Reorder the terms:
6 + -12 + a = 2

Combine like terms: 6 + -12 = -6
-6 + a = 2

Solving
-6 + a = 2

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + a = 2 + 6

Combine like terms: -6 + 6 = 0
0 + a = 2 + 6
a = 2 + 6

Combine like terms: 2 + 6 = 8
a = 8

Simplifying
a = 8

See similar equations:

| 9-4(3x+7)=26 | | 14(-17x+16)= | | (3m+13)-(4m+6)= | | 5w(3w+6)= | | -14-4*3= | | 8-(4x+1)=5(x+6)-2 | | 15-40=m | | -3x^5-3x^4+8x^2-12= | | -31=-7+4y | | 30a-18=3 | | (9m-6)7= | | -14+4*3= | | x-2+x-2+x-1+x-1=p | | 16-4x=-2(2-8) | | -8(w-20)=.96 | | x(y)=25 | | -4-3+(-14)= | | (17b-1)-4(4b+4)=-3 | | ln(3x)-ln(x-8)=ln(x+5) | | 4x-10=7x-29 | | 2y-12=-12 | | -4-8=t | | y-1+2y-7=180 | | -12=3(x+4)+3x | | 446=x^2 | | (9x-2)+(7x+14)=180 | | -17(-13-12q)= | | 54=3g | | -15x+10=15x-10 | | Y-8=2(x-6) | | 9t-13t=24 | | 4(n+4)-6u=14 |

Equations solver categories